Visitantes florais e polinização de Tecoma stans (Bignoniaceae): efeito da pilhagem de néctar na eficácia reprodutiva - Santos, Jean Miguel Alves dos (2016)
Bees are the main pollinators of plant species of agricultural system and most terrestrial environments, interacting with native and exotic plants. Exotic plants are usually found in urban areas, like Tecoma stans, an introduced ornamental species in Brazil, native from the southern United States and northern Central America. In flowers with long tubular corolla as T. stans it is common to certain species of bees make openings/holes that enable access to the floral resources. However, as they do not enter the flower, these bees perform illegitimate visits, because they do not contact the reproductive structures of flowers, and thus rob the floral resources without pollinate the flowers. However, no studies on the robbing behavior in this species has been done. Studies show that the robbing behavior of pollen and nectar can benefit, be neutral or decrease the reproductive success of other plant species. Some studies have been published on the interaction of bees with this plant, mainly in the region south and southeast of Brazil. The objective of this research was to study the bee species assemblage that visit the flowers of Tecoma stans in two areas with different characteristics emphasizing the robbing behavior and its consequences. The study was carried out at the Campus I of the Universidade Federal da Paraíba (UFPB), João Pessoa - PB, and the Sítio Olho D'água, Alhambra - PB, during October 2014 and November 2015. All the manual pollination tests resulted in fruit yield while spontaneous self-pollination did not yield fruits, confirming that Tecoma stans is auto-compatible, but needs pollinators to transfer the pollen grains. After floral anthesis, the flowers last for two days and provide pollen for its visitors, an average of 4064.9±543.9 grains/anther; and nectar, mean production of 14.4±7.3μl/day, with an average concentration of sugar of 21.3±3,8% and 0.47±0.3mg of sugar/μl. 24 species of bees were recorded in UFPB and 21 species at the Sítio Olho D'água. The bees started foraging around 5:00h till 17:30h. Visits and visitors were more constant in UFPB than at the Sítio Olho D'água that showed greater variation during the day The number of visits and visitors were significantly higher in UFPB. Peak of visitors occurred in the flowers at 8.00h (average of 9.3±8.3 visitors/plant/day in UFPB. While at the Sítio Olho D'água there was a mean peak of visitors at 8:00h and 12:00h, average of 5.6±2.4 visitors/plant/day and 4.9±2,7 visitors/plant/day, respectively. The most abundant bee species were Trigona spinipes, T. fuscipennis, Partamona littoralis, Plebeia flavocincta and Xylocopa spp. in UFPB, and M. scutellaris and Augochlora spp. in Sítio Olho D'água. Eulaema nigrita, E. atleticana, Centris analis, C. fuscata, C. tarsata, C. aenea, Euglossa carolina, M. scutellaris and Melitoma segmentaria were considered effective pollinators. Apis mellifera, Augochlora sp., Ceratina chloris, C. maculifrons, Nannotrigona punctata, Partamona littoralis, Plebeia flavocincta, Trigona spinipes and T. fuscipennis were classified as occasional pollinators. Females of Xylocopa spp., Pseudaugochlora spp. and Trigona spinipes were primary nectar robbers. Trigona spinipes and Trigona fuscipennis were primary pollen robbers. In experiments in which the flowers received a barrier to prevent nectar robbing, the Reproductive Success of open-pollination with and without barrier were low and similar in both areas, suggesting that the nectar robbing did not influenced the production of fruits, refuting the hypothesis proposed. However, in later tests the Reproductive Success and Reproductive Efficacy in flowers was higher without barrier suggesting that the nectar robbing favored pollination supporting the hypothesis tested. This difference in results may be related to different periods of carrying out the tests, as well as differences in the abundance and pollinator composition in each area. Although some results showed that nectar robbing can affect negatively the fruit production of T stans, we still need more conclusive experiments.